### Discussion :: Numbers - General Questions (Q.No.138)

Shahid said: (May 20, 2011) | |

[(a + b)2 - 4ab]=[(a-b)^2] From the above we have a=476 ,b=424 so Result is (476-424)^2 =52^2=2704 |

Arif said: (Sep 12, 2011) | |

[(a+b)^2-4ab]=a^2+b^2+2ab-4ab =(a-b)^2 =(476-424)^2 =52^2 =2704 |

Siva said: (Aug 18, 2014) | |

[(a+b)^2-4ab] = a^2+b^2+2ab-4ab. = (a-b)^2. = (476-424)^2. = 52^2. = 2704. |

Ipsita said: (Feb 1, 2016) | |

But as we know: (a-b)^2 = a^2-2ab+b^2. |

Bindu said: (May 19, 2016) | |

This is in the form of (a + b)^2 - 4ab. So, (a^2 + b^2 + 2ab - 4ab). = a^2 + b^2 - 2ab. = (a - b)^2. So, a = 476, b = 424 by substituting the value we get the answer. = 2704. |

Pritam said: (Mar 14, 2017) | |

Nice and easy method @Bindu. |

Krishna said: (Aug 17, 2018) | |

4ab=(a+b)^2-(a-b)^2. Thus (a+b) ^2-4ab=(a-b)^2.. a-b=476-424=52. 52^2=2704 =>answer. |

Suraj said: (Sep 12, 2018) | |

Sum of two numbers is twice their difference. If one of the number is 10then the other no is? Please, anyone, answer this. |

Swar said: (Dec 12, 2018) | |

@Suraj. Let two numbers be considered as x and y As per question ,x+y=2(x-y) , Given one numbers as 10, 10+y=2(10-y), 10+y=20-2y, 2y+y=20-10, 3y=10, Y=10/3. Correct me, if I am wrong. |

#### Post your comments here:

Name *:

Email : (optional)

» Your comments will be displayed only after manual approval.